2016
DOI: 10.18632/oncotarget.13393
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin inhibits STAT3 and exhibits anticancer potential in human triple-negative breast cancer therapy

Abstract: Triple-negative breast cancers (TNBCs) are the most aggressive and hard-to-treat breast tumors with poor prognosis, and exploration for novel therapeutic drugs is impending. Arctigenin (Atn), a bioactive lignan isolated from seeds of Arctium lappa L, has been reported to inhibit many cancer types; however, the effect of Atn on TNBC remains unclear. In this study, we demonstrated that Atn decreased proliferation, and induced apoptosis in TNBC cells. Furthermore, we explored the underlying mechanism of Atn inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 46 publications
2
47
1
Order By: Relevance
“…Atn was identified to inhibit STAT3 binding to genomic DNA by disrupting hydrogen bond binding between DNA and STAT3. In addition, Atn augmented Taxotere ® -induced TNBC cell cytotoxicity (18). Here, we further showed that Atn was also able to cause a significant dose-and time-dependent decrease of CIP2A at both mRNA and protein levels in TNBCs (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Atn was identified to inhibit STAT3 binding to genomic DNA by disrupting hydrogen bond binding between DNA and STAT3. In addition, Atn augmented Taxotere ® -induced TNBC cell cytotoxicity (18). Here, we further showed that Atn was also able to cause a significant dose-and time-dependent decrease of CIP2A at both mRNA and protein levels in TNBCs (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Atn can also enhance the chemosensitivity of several cancer cells (Hepg2, HeLa, and K562), to cisplatin by inhibiting the STAT3 signaling pathway at high doses (17). As we showed in our previous study (18), Atn inhibited cell growth and induced apoptosis in TNBCs by inhibiting STAT3. We used computational docking and molecular dynamics simulation showed that Atn had high-affinity interaction with the SH2 domain of STAT3 with residues (Arg688, Pro689, and Pro695).…”
Section: Introductionmentioning
confidence: 54%
“…As mentioned above, several studies have showed that apoptosis induction is a key mechanism of arctigenin to exert anticancer activities (Feng et al, ; Hsieh et al, ; Wang, Solorzano, et al, ). In the present study, we compared apoptosis induction by the 3′‐DMAG with that of arctigenin and found that 3′‐DMAG induced a quadrupling higher apoptosis than that by arctigenin.…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin exhibits distinct biological activities, including antiviral (Dias et al, ; Hayashi, Narutaki, Nagaoka, Hayashi, & Uesato, ), neuroprotection (Song et al, ; Zhu et al, ), antidiabetic (Huang et al, ; Zeng et al, ), and anticancer (Chen et al, ; Huang et al, ; Hsieh et al, ; Jeong, Hong, Jeong, & Koo, ; Lei, Gan, Zhao, Yu, & Hu, ; Li, Liang, Tian, & Hu, ; Maimaitili et al, ; Wang, Solorzano, et al, ; Susanti et al, ). A growing body of literature documents that arctigenin can induce cell cycle arrests, apoptosis, autophagy, and antimetastasis in multiple types of cancer cells, including prostate (Wang, Solorzano, et al, ), breast (Feng et al, ; Hsieh et al, ; Lou, Zhu, Zhao, Zhu, & Zhao, ; Maxwell, Lee, Kim, & Nam, ), lung (Lei et al, ), liver (Susanti et al, ), gastric (Jeong et al, ), ovarian (Huang et al, ), colon cancer (Li et al, ), and glioma (Maimaitili et al, ). The anticancer efficacy of arctigenin in vivo also has been reported in human cancer cell xenograft model in athymic nude mice (Feng et al, ; Wang, Solorzano, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation